Students' Barrier and Motivation Regarding English Online Learning during the COVID-19 Outbreak - Indah Mahmuda; Ahmad Syauqi Harsyah; Siti Aminah (Institut Agama Islam Negeri Palopo, 2023)
The aim of this study was to analyze students’ barrier and motivation regarding English Online Learning during the COVID-19 outbreak. The subject of the research was eleventh-grade students at SMA Negeri 1 Batang Hari in academic year of 2020/2021. This research employed a descriptive research method using quantitative and qualitative techniques to explore and explain students’ barrier and motivation. Based on the data presentation and analysis of the research, it can be concluded that Eleventh graders at SMA Negeri 1 Batang Hari encounter barriers regarding online learning during the COVID-19 outbreak such as condition for accessing the internet, deficiency in using the online learning application used by the teacher, the courseware is too rigid and becomes a burden, the learners did not know how to get help from the teacher, and the learners did not know how to get help from the teacher. Besides that, several motivations are also identified in this study, they are: (1) The students were willing to study English using the media chosen by their teacher, as long as it is easy to use. (2) Majority of students ask their English teacher when they had difficulty in learning English through online learning. (3) Majority of students were always working on English assignments given by the teacher because they were afraid of their parents and teacher. (4) They will try as best as they can in completing the assignments. (5) Most of the students were motivated and enthusiastic to study English through online learning.